Application of physiologically based pharmacokinetic modelling for the prediction of drug–drug interactions involving anlotinib as a perpetrator of cytochrome P450 enzymes. Issue 5 (22nd March 2022) - Jin, Zhiping; He, Qingfeng; Zhu, Xiao; Zhu, Mingshe; Wang, Yike; Wu, Xin‐an; Lv, Qianzhou; Xiang, Xiaoqiang
Abstract: Anlotinib is a small molecule of novel tyrosine kinase inhibitor initially approved to treat non‐small cell lung cancer in China. Drug–drug interaction (DDI) is an extrinsic factor important for the appropriate use of anlotinib in clinical practice. In vitro experiments demonstrated that anlotinib is a substrate of cytochrome P450 (CYP) enzymes and moderate inhibitor of several common ones; however, no clinical DDI studies have been performed to investigate inhibitory effects of anlotinib on these CYP enzymes. Thus, its drug label recommends avoiding co‐administration with substrates of these enzymes, which have narrow therapeutic windows. In this study, we performed a CYP450 inhibition study, followed by gathering in vitro and clinical pharmacokinetic data to build the first physiologically based pharmacokinetic (PBPK) model of anlotinib. The verified model was subsequently used to predict the DDI mediated by anlotinib. As a result, the marginal plasma exposure changes of typical CYP3A and CYP2C9 substrates were less than the bioequivalence threshold, indicating that anlotinib has a very low potential of causing clinically meaningful DDI through the inhibition of several major CYP enzymes. According to the FDA's latest guideline on DDI, the established model with the simulation results may support the revision of anlotinib labelling without further clinical studies, lifting unnecessary restrictions on anlotinib regimens.